PENDAMPINGAN PENGUATAN STRATEGI BERTAHAN USAHA MIKRO BONTOT DOMAS DALAM MENGHADAPI PERSAINGAN KULINER MODERN UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA DOMAS - Michael Tedi Fernando Gurning; Heru Ahya; Muchyar Hadi; Ade Fauzi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting local economic development and preserving traditional products. This community service activity was conducted with Bontot MSMEs in Domas Village, Pontang District, Serang Regency, Banten Province. The activity aimed to strengthen business sustainability strategies, improve marketing capabilities, and enhance the competitiveness of traditional culinary products. The methods and prosedures used included observation, interviews, socialization, and mentoring through a participatory approach. The results showed that Bontot business actors have implemented various survival strategies, such as maintaining product quality, improving customer service, utilizing social media promotion, and managing production efficiently. The activity also increased participants’ understanding of digital marketing, business development, and local economic potential. Furthermore, the existence of Bontot MSMEs contributes to employment opportunities and supports the local fisheries supply chain. Therefore, strengthening MSME capacity is essential to ensure business sustainability and community welfare.